EDUKASI POLA HIDUP BERSIH DAN SEHAT BAGI ANAK USIA DINI DI RAUDLATUL ATHFAL AL-MUNAWWAROH JABUNG PONOROGO - Retno Pratiwi; Siti Soraya (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2022)
During the Covid-19 pandemic, everyone must give physical health and environmental hygiene great attention. Parents and educators need to teach early childhood to start getting used to a healthy lifestyle from an early age. This community service aims to increase awareness by habituating a clean and healthy lifestyle in Raudlatul Athfal Al-Munawwaroh, Jabung village, Mlarak, Ponorogo. The method used in this service is the Asset Based Community Development (ABCD) approach with the Appreciative Inquiry (AI) model. 21 students attended this activity. The service result indicated an increase and students' understanding every day about the importance of implementing a clean and healthy lifestyle. In implementing the habituation of a clean and healthy lifestyle, there needs to be cooperation between parents, educators, students, and school policies.